Implementation of Web-Based System for Pigeon Post Competition in Galaxy Community - Dhanar Intan Surya Saputra; Yudhistira Janice Al Sava; Yusmedi Nurfaizal; Didit Suhartono; Sitaresmi Wahyu Handani (Jurnal Pengabdian dan Pemberdayaan Masyarakat Indonesia, 2021)
Pigeons Post are sophisticated birds with a good memory, navigation skills and an instinct to return to the nest after a long absence. Over time, has become popular as a pet, and a sport. In Indonesia, the Pigeons Post championship is legally protected through POMSI (in Bahasa Indonesia: Perkumpulan Olahraga Merpati Pos Seluruh Indonesia), held by local, and national communities, this hobby continues to grow. This competition technique is that participants register, bring the bird to a place have prepared, and fly it with applicable conditions. Many competition participants cause problems because the conventional processes lead to data entry errors, flight speed calculations, lost registrations, and human errors. This community service activity is to help, and facilitate the implementation system of the Pigeons Post competition in the community - POMP Galaxy (in Bahasa Indonesia: Perhimpunan Olahraga Merpati Pos). The results prove that the system has been created to facilitate the committee in managing and improving the competition's judging accuracy. This system is tested using alpha testing, which shows all features are running well. On the other hand, the acceptance test results through the questionnaire resulted in a response percentage of 89.99%, with the system's calculation criteria strongly agreeing.